2017
DOI: 10.18632/oncotarget.19473
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of resveratrol against light-induced retinal degeneration in aged SAMP8 mice

Abstract: PurposeThe purpose of this study was to determine the protective effects of Resveratrol (RESV) on acute bright light-induced retinal degeneration in aged senescence accelerated mouse strain.MethodsTen three-month-old male SAMP8 mice (prone to aging) were randomly assigned to two experimental dietary groups: one untreated group and one RESV treatment group (n=20 eyes for each group). After 30 days of treatment, mice were exposed to intense bright light. Ten male SAMR1 mice (resistant to aging) served as control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Canonical WNT signaling pathway inhibition and many kinds of kinases activation participate in the therapeutic effects [ 28 32 ]. Resveratrol treatment decreases a series of cytokines, including decreased IL-6, IFN-γ, TNF-α and Oncostatin M [ 33 , 34 ]. However, exact mechanism of CSCs elimination is rarely reported in resveratrol treated osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Canonical WNT signaling pathway inhibition and many kinds of kinases activation participate in the therapeutic effects [ 28 32 ]. Resveratrol treatment decreases a series of cytokines, including decreased IL-6, IFN-γ, TNF-α and Oncostatin M [ 33 , 34 ]. However, exact mechanism of CSCs elimination is rarely reported in resveratrol treated osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Retinari™ treated NFE2L2 KO mice presented with a highly significant increase of scotopic a-and b-wave amplitudes as well as thicker TRT in OCT. A similar increase was observed for photopic ERG b-wave amplitudes. Previous studies reveal that resveratrol increases b-wave amplitudes and contributes to a thicker outer nuclear layer in the aged mouse retina [51,52]. Retinal thickness across the retina has been shown to decrease with age [53], and it is related to AMD progression [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol in turn has been linked to antioxidant defence and autophagy enhancement as well as inflammatory response regulation, including CFH-linked complement system modulation [40,68,69]. Furthermore, improved ERG function has also been associated with resveratrol in aged rats [70] and mice with light-induced retinal degeneration [51,52]. All molecular characteristics mentioned above are in logical continuum generating a treadmill worsening the situation on the retina in every turn.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have indicated that resveratrol causes a reduction in IOP in steroid-induced ocular hypertension rats [73] and normal normotensive rabbits [74]. Resveratrol has neuroprotective effects through suppressing apoptosis-related molecule activator protein 1 (AP-1) [75] and elevating neuroprotective factors such as leukemia inhibitory factor (LIF), brain-derived neurotrophic factor (BDNF), oncostatin M (OSM), cardiotrophin 1 (CT-1), and cardiotrophin-like cytokine (CLC) [76] in light-induced retinal degeneration mouse models. It has also demonstrated benefits in alleviating hyperglycemia, oxidative biomarkers, vascular damage, anti-inflammation, anti-apoptosis, and reduction in the thickness of retinal layers in DR animal models.…”
Section: Resveratrolmentioning
confidence: 99%